Increased Survival after Treatment of Canine Hemangiosarcoma with Fenofibrate - Johanna K Ecke; Luis Del Valle; Amanda Parker Struckhoff; Piotr Waligorski; Krzysztof Reiss; Francesca Peruzzi (International Journal of Veterinary Science and Research - Peertechz Publications, 2015)
Hemangiosarcoma (HSA) is a common and highly metastatic tumor that affects predominantly large-breed dogs. The median survival time for dogs diagnosed with splenic HSA without adjuvant chemotherapy after surgery is 86 days. Fenofibrate is an FDA-approved drug commonly utilized to treat high cholesterol and high triglyceride levels in humans. However, fenofibrate has also been shown to possess anti-proliferative and anti-metastatic properties against several aggressive and highly metastatic tumors in vitro and in small animal models.We report a case of a 6.5-year-old dog diagnosed with a splenic hemangiosarcoma and treated solely with micronized fenofibrate, administered orally once a day following splenectomy. The dog survived for over 26 months (804 days) after initial diagnosis without signs of adverse effects due to fenofibrate treatment